Effects of respiratory endurance test detected by surface electromyography (sEMG) in patients candidates for liver transplantation - Custódio, Sulaine Rodrigues; Santos, Rafaela Brunetti dos; Silva, Áurea Maria Oliveira da; Ratti, Lígia dos Santos Rocetto; Boin, Ilka de Fátima Santana Ferreira; Duarte, Rayssa Pistilli; Tonella, Rodrigo Marques (Brazilian Journal of Transplantation, 2016)
Purpose: To analyze the repercussions of the endurance test in the inspiratory muscle with Powerbreathe device on the diaphragm through the IPmax and RMS (Root Mean Square) values of the surface electromyography (sEMG) in patients preoperatively to liver transplantation. Materials and Methods: Prospective study performed at the Gastrocentro Ambulatory of Clinical Hospital of UNICAMP. Eleven individuals candidates for liver transplantation of both genders, who signed the consent term were selected. They were submitted to anthropometric assessment, pulmonary function test, IPmax measurements and a surface electromyography performed. Results: The measured IPmax values showed that there is a decrease in inspiratory muscle strength both for men and women. In the right dome, it was observed that when the unloaded moment was compared to Time 1, there was a significant reduction in the RMS values (p = 0.008) and by comparing Time 1 and Time 2, there was a significant increase in the RMS (p =0.006). When comparing the value at the unloaded time with Time 1 in the left dome, there was a significant reduction in the RMS values (p = 0.0009), and in the comparison between Time 1 and Time 2, there was a significant increase in the RMS (p = 0.0009). Conclusion: It was possible to observe that the IPmax values were unable to detect the fatigue imposed by the test. On the other hand, EMS values were sensitive in detecting diaphragmatic muscle fatigue after the endurance test.